The application of bleu metric to evaluate the translation quality of google translate on Amazon.com: a case study on English - Vietnamese translation on beauty & personal care products’ description = Ứng dụng thuật toán Bleu để đánh giá chất lượng bản dịch của google dịch trên Amazon.com: nghiên cứu trường hợp điển hình: bản dịch anh việt của phần mô tả sản phẩm thuộc các sản phẩm làm đẹp - Khúc, Thị Quỳnh Trang (2020)
The utilization of online machine translation tool has come to its fullest bloom, which is not only signified by the substantial quantity of tools, but also by the increasing usage frequency of humankind. Along with the popularity of translating tools, there are in fact some skeptical ideas on the translation quality of these online tools, especially when applying in practical circumstances. In response to those doubts, this research chooses to evaluate one of the most commonly used translation tools – Google Translate. This tool is assessed in the context of Amazon.com website, a well-known e-commerce platform in Vietnam. The researcher employs an automatic evaluation tool named Bilingual Evaluation Understudy (BLEU) to evaluate a number of 176 translations by Google Translate. Their BLEU score results prove that the quality of Google Translate has reached an acceptable level, yet its performance is observed to vary according to the length of source texts.